Sensory, Textural and Cooking Quality of Instant Noodles Produced from Musa spp - Wheat Composite Flours - Adebayo, W. A.; Ogunsina, B. S.; Taiwo, K. A. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2018)
Enormous post-harvest losses (35 - 60%) associated with banana and plantain products in Nigeria and other producing countries in the tropics culminate in great losses for farmers. In Nigeria, unripe plantain is normally processed into flour with limited consumption only as reconstituted dough in local food systems. Previous studies established that Nigerians have acquired taste for noodles and it is widely consumed across all strata of the economic divide. Information regarding the production of instant noodles from Musa spp. is rarely found in literature; hence in this study the quality characteristics of instant noodles produced from Musa spp – wheat composite flours was investigated. Musa spp – wheat composite flours in the ratios 0:100; 5:95; 10:90; 15:85; 20:80 and 25:75 were processed into instant noodles. The proximate composition, sensory, textural and cooking quality of the instant noodles were determined following standard procedures. The results showed a corresponding increase in the crude fat, ash and fibre contents of instant noodles as the percentage substitution with Musa spp flour in the instant noodle formulation increased. Significant differences (p<0.05) were observed in the taste, colour, flavor, texture and overall acceptability of the products. It was observed that cooking time and cooking loss decreased from 4.38 – 3.40 min and 7.61 – 5.51% as percentage substitution increased, respectively; whereas cooking gain, moisture and fat uptake increased as substitution level increased. The force–deformation curve of Musa spp - wheat instant noodle obeyed the Hooke’s law showing a decrease in the strength characteristics of noodles as percentage substitution with Musa spp flour increased. The production of instant noodles from banana and plantain offers means of promoting and extending its utilization, thereby boosting the income obtainable from its production.